Application of Speech Recognition for Swiftlet Vocalizations - Siti Nurzalikha Zaini, Husni Zaini; Sunardi, S.; Kamarul Hawari, Ghazali; Saiful Nizam, Tajuddin (2013)
This research is about speech recognition technique are used for swiftlet vocalization application. Swiftlet vocalization need a system for recognize because there are many types of swiftlet sounds use in industry only can inspection by human expert. This research use speech recognition by using Mel Frequency Cepstral Coefficient (MFCC) for feature extraction and Distance Time Warping (DTW) for classification to calculate accuracy and efficiency combination both techniques.